Individualismo e alteridade nos vínculos afetivos-sexuais sob o olhar de mulheres adultas - Figueredo, Beatriz Soledad Merino (Universidade Federal de São Carlos, 2024)
At the turn of the 21st century, Information and Communication Technologies (ICTs) emerged as a factor that profoundly influences contemporary sexuality, especially with the popularization of the internet and digital platforms. The aim of this study was to understand affective relationships initiated through digital platforms in order to analyze their trajectory and path. Eight women were interviewed, aged between 21 and 30, heterosexual or bisexual, who had been in stable relationships for two years or more and who met their partners through social networks. The remote interviews were conducted according to a semi-structured script, recorded and transcribed in full. The data was analyzed according to thematic analysis. The research protocol was approved by the Human Research Ethics Committee (CEP) of the Pro-Rectory of Research (ProPq) of the Federal University of São Carlos (UFSCar) (CAAE No. 68823423.0.0000.5504). The following categories were compiled: narcissism, sublime love and relationship history. The results reveal that the construction of affective-sexual relationships is based on the challenging balance between otherness (respect for the idiosyncrasies/singularity of the partner) and narcissism (the search for satisfaction of one's own rights/desires). Some couples remain stuck in narcissistic patterns, where partners seek to satisfy their own desires/needs, treating the other as a means to achieve them. However, couples whose bond is built on understanding each other's limits, recognizing and valuing differences seem to have better levels of affective-sexual satisfaction.
Individualism and otherness in affective-sexual bonds from the point of view of adult women
Keywords: Amor; Narcisismo; Alteridade; Relacionamento virtual; Psicanálise; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO